Community Leaders' Views on Water Quality BMPs in Kansas - Steve Hill; Terrie Clark; Ted Cable; Kris Boone; Pat Melgares (Journal of Applied Communications, 2006)
Determining which strategic communications efforts can encourage environmentally sustainable behavior requires information on barriers to that behavior. To help assess a Kansas water quality program, researchers examined focus group data from community leaders interested in water issues. Working within the context of the theory of planned behavior and two broader conceptual frameworks, researchers found several major themes indicating support for a broad-based approach to water quality programs. Themes included concepts of home and place, awareness and understanding, relationships, ownership of issues, and money. Findings generally confirmed the need to emphasize multiple points at which intervention strategies can occur, including communication and diffusion instruments. Improved educational programs, informational efforts aimed at urban audiences and producer groups, and use of local information sources were cited as areas in which communications efforts would be valuable in water quality programs.